1999
DOI: 10.1007/pl00010295
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Triazenopyrazole Derivativesas Potential Inhibitors of HIV-1

Abstract: Ethoxymethylenemalononitrile and bis(methylthio)methylenemalononitrile were condensed with hydrazine hydrate to yield 5-aminopyrazole-4-carbonitrile (3a) and 5-amino-3methylthiopyrazole-4-carbonitrile (3b), respectively. These compounds were treated with nitrous acid and coupled with different secondary amines to yield the triazenopyrazoles 4a±j. 5-(3,3-Diethyl-1-triazeno)pyrazole-4-carbonitrile (4c) was transferred into its two regioisomeric 2deoxyribose nucleosides 5a,b which were subsequently hydrolyzed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 1 publication
1
28
0
Order By: Relevance
“…2 Various 4,5-diaminopyrazoles have been reported as intermediate in the synthesis of 1,2,4-triazoles, 3 imidazo [4,5-c]pyrazoles 4 and benzodiazepines. 5 These fused systems have been evaluated as anti-cancer activity, 6 anti-HIV inhibitors, 7 antiasthmatic and antinflammatory activity. 8 The 4,5-diaminopyrazoles were reported by preparation of different methods.…”
Section: Introductionmentioning
confidence: 99%
“…2 Various 4,5-diaminopyrazoles have been reported as intermediate in the synthesis of 1,2,4-triazoles, 3 imidazo [4,5-c]pyrazoles 4 and benzodiazepines. 5 These fused systems have been evaluated as anti-cancer activity, 6 anti-HIV inhibitors, 7 antiasthmatic and antinflammatory activity. 8 The 4,5-diaminopyrazoles were reported by preparation of different methods.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of triazenes as versatile tools in organic synthesis has also been reviewed recently [3]. Triazenes [4] and chemical compounds with benzenesulfonamide groups have interesting biological properties and potential applications as drugs [5]. Previous theoretical studies on triazene systems have been reported *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…31 In the following step, compounds 4 and 2 underwent cyclization under mild acidic condition at reflux to yield 7-(3-nitro-phenyl)-pyrazolo[1,5-a]-pyrimidine-3-carbonitrile (5). 29 An efficient reduction of 5 using 10% Pd/C catalyst at an H 2 pressure of 60 psi gave 7-(3-amino-phenyl)-pyrazolo[1,5-a]pyrimidine-3-carbonitrile (6).…”
mentioning
confidence: 97%